Pengaruh Koneksi Politik terhadap Tingkat Real Earnings Management di Indonesia - Feby Astrid Kesaulya; Weny Putri; Khairunnisa Khairunnisa (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2023)
The Objective of this research was to prove that there is a correlation between political connections with real earnings management. Some of the previous research had shown the result that political connections positively effected earnings management level, but some others found different results. Political connections in this research were measured by the sum of politically connected board of director and politically connected board of commissioner. This research was conducted in Indonesia using publicly listed manufacture companies. A total sample in this research is 297 firm years. The results of this research are not supported the hypothesis which was previously developed. This research showed that both politically connected board of director and politically connected board of commissioner are not affected the real earnings management practices. It can be resulted from the insignificant number of politically connected board of director and politically connected board of commissioner in the sampel. So that the political connection could not be the predictor of real earnings management in this research.